1/6x-3=4

Simple and best practice solution for 1/6x-3=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6x-3=4 equation:



1/6x-3=4
We move all terms to the left:
1/6x-3-(4)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
We add all the numbers together, and all the variables
1/6x-7=0
We multiply all the terms by the denominator
-7*6x+1=0
Wy multiply elements
-42x+1=0
We move all terms containing x to the left, all other terms to the right
-42x=-1
x=-1/-42
x=1/42

See similar equations:

| 3/2(x−2)−5=19x | | 32(x−2)−5=19x | | 3(x+2)=(3x-4) | | 7.7-0.5x=4.7 | | 3^(4-x)-7=74 | | 5(4x-1.5x)+12=12=4x-2 | | 25-30x=65+20x | | 16y-6=14 | | 5.45+x=8 | | (3m+1)(-2)=11 | | 3(6x-3)=99 | | 0.7=y/4 | | 2/3=1/3(x-4) | | 4.7=7.7=0.5x | | 2x-5=10x+20 | | 3/5=3/5x+4 | | 6m(m-6)=0 | | 4g+3.72=20.84 | | -2(3a-2)=88 | | 54+m=73 | | D=166t^2 | | -2v–3v=45 | | 2(3+4m)-9=5 | | 0.09+0.13(k+300)=61 | | -34+n=15 | | 5/12(x)=-0.75 | | 9w-14=-4 | | 20.84=4g+3.72 | | 16x+1=28x+3 | | 28x+3=16x+1 | | 4t+5=8t+4 | | 4x-6x=25 |

Equations solver categories